The reality of the organizational environment for educational supervisors from the point of view of physical education teachers in Baghdad - Mohammed , Nadia; mutib, suher (Journal of Physical Education, 2024)
The aim of the research to identify the details of the reality of the organizational environment for educational supervisors from the point of view of physical education teachers in Baghdad, and the two researchers relied on the descriptive approach on a sample chosen randomly from teachers and teachers of physical education who are continuing their time in their primary schools for the academic year (2023/2024), the total number ( 1730) individual, and they are distributed by (180) primary schools in the six education directorates in the capital, Baghdad, who are actually continuing the official working hours of the permanent owners and the number of those who number (1562) individuals, who were chosen for the survey Sam (0.694 %) of their origin society, as was chosen for the application sample (450) individuals included in the research in various schools of education directorates in the capital, Baghdad, and they represent (26.012 %) of their origin society, After the adoption of the organizational environment scale for educational supervisors, the main survey of the time period was conducted from Monday, corresponding to the date (4/8/2024) until Monday, corresponding to the date (6/4/2024), and results were addressed using the statistical bag system (SPSS) to be The conclusions and recommendations are that the educational education supervisors are an intermediate level of the organizational environment from the point of view of physical education teachers in Baghdad, and the point of view of physical education teachers in Baghdad has achieved an advanced level of the possession of educational physical education supervisors to justice the recommendation of the reward that raises the level of the organizational environment phenomenon, Raising the level of the organizational environment for educational education education supervisors needs to pay attention to organizational standards from the point of view of physical education teachers in Baghdad, and it is necessary to work to raise the organizational environment for educational education education supervisors because of its role in raising the level of change management they have to better levels, It is necessary to work to raise the level of organizational standards for educational education supervisors, because of the importance of raising the level of the organizational environment for them, and it is necessary to find ways to build direct cooperation seminars between the six directorates of education in the capital, Baghdad, with academics specialized in sports administration directly, to provide them with what It is new to raise the level of the organizational environment and the management of change for educational education supervisors